On the existence of periodic solution of some quasilinear differential equations with impulses - Tai, Le Luong (Vietnam Journal of Mechanics, 2004)
As for ordinary differential equations, one of the problems that especially attract the attention of many mathematicians is the problem on the existence of periodic solutions of the differential equation systems with impulses. In this paper, we study the periodic solutions of the equation system under of the form...